(untitled) (Doctor Virtualis, 2024)
Most of Dante’s biographers accepted as possible the account of the journey to Paris, as narrated – among others – by Boccaccio. The issue seems relevant considering the circumstances that may have prompted the Poet to travel to France. Could he have been determined by stories heard about the emergence of new political ideas among some of the Parisian masters? Who could have aroused Dante’s curiosity and how would the Poet then attempt to reveal to his readers what he had learned? This article intends to provide an interpretation of ‘Paradiso’ XVIII, focusing on a few obscure verses related to the bella image of the Eagle that, in the following cantos, will pronounce two speeches, saying ‘io e mio’,/ quand’era nel concetto e ‘noi e nostro’.